A guide into glycosciences: How chemistry, biochemistry and biology cooperate to crack the sugar code - Solís, Dolores; Bovin, Nicolai V.; Davis, Anthony P.; Jiménez-Barbero, Jesús; Romero, Antonio; Roy, René; Smetana, Karel; Gabius, Hans-Joachim (Biochimica et biophysica acta, 2015)
The most demanding challenge in research on molecular aspects within the flow of biological information is posed by the complex carbohydrates (glycan part of cellular glycoconjugates). How the ‘message’ encoded in carbohydrate ‘letters’ is ‘read’ and ‘translated’ can only be unraveled by interdisciplinary efforts. This review provides a didactic step-by-step survey of the concept of the sugar code and the way strategic combination of experimental approaches characterizes structure–function relationships, with resources for teaching. The unsurpassed coding capacity of glycans is an ideal platform for generating a broad range of molecular ‘messages’. Structural and functional analyses of complex carbohydrates have been made possible by advances in chemical synthesis, rendering production of oligosaccharides, glycoclusters and neoglycoconjugates possible. This availability facilitates to test the glycans as ligands for natural sugar receptors (lectins). Their interaction is a means to turn sugar-encoded information into cellular effects. Glycan/lectin structures and their spatial modes of presentation underlie the exquisite specificity of the endogenous lectins in counterreceptor selection, that is, to home in on certain cellular glycoproteins or glycolipids. Understanding how sugar-encoded ‘messages’ are ‘read’ and ‘translated’ by lectins provides insights into fundamental mechanisms of life, with potential for medical applications. •The inherently interdisciplinary character of glycosciences is explained on an educational level.•Lectin structure and functionality are presented from synthetic receptors to clinically relevant human proteins.•Methods to study protein–glycan interactions are presented in a problem-oriented manner.